Investigation on close-coupled gas atomization for Fe-based amorphous powder production via simulation and industrial trials: Part I. Melt breakup behaviors during primary atomization - Jiaqi Liu; Pu Wang; Yannan Dong; Huan Zhao; Jing Pang; Jiaquan Zhang (Journal of Materials Research and Technology, 2023)
The primary atomization process is simulated by Volume of Fluid (VOF) model and dynamic adaptive mesh method. The influence of melt mass flow rate and atomization pressure on the breakup process is investigated, and the effect of hot gas atomization is also evaluated. The results show that the breakup is insufficient when the melt mass flow rate is larger than 0.075 kg s−1, while the liquid film breakup inducing the nozzle clogging occurs when the melt mass flow rate is too low (0.025 kg s−1). The backflow of droplets occurs at low atomization pressure (1.0 MPa), and various defects (satellite powders, hollow powders and needle-shaped powders) appear when the atomization pressure is larger than 3.0 MPa. Although the breakup efficiency can be significantly improved by increasing the gas temperature, severe deformation of the gas-liquid interface is induced due to the Kelvin–Helmholtz wave and gas-liquid interaction, easily leading to the formation of hollow powders. Besides, the gas-to-melt ratio (GMR) is identified as a simple criterion for predicting primary atomization breakup modes, with liquid film breakup occurring when GMR≥4.4 and ''fountain'' breakup occurring when GMR≤4.3. In this work, not only the gas-liquid interaction is systematically analyzed by establishing a flow-heat transfer-VOF coupling model, but also the GMR is proposed to predict the breakup mode in the industrial production, which can provide theoretical and methodological guidance for the optimization of atomization operational parameters.